(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to examine the effectiveness of a counseling program based on cognitive-behavioral techniques in reducing future anxiety among a sample of Tobruk University students and to explore the continuity of its effect over time. The study followed a quasi-experimental design with two groups (experimental and control) and three measurements (pretest, posttest, and follow-up). The sample consisted of 30 students, equally divided into two groups. The experimental group received a 10-session cognitive-behavioral counseling program, while the control group received no intervention. The findings revealed statistically significant differences between the pre- and post-measurements of the experimental group in favor of the post-measurement, indicating the program’s effectiveness in reducing future anxiety. Furthermore, the impact of the program was maintained in the follow-up measurement after one month. No significant changes were observed in the control group. The study recommends implementing such counseling programs in educational institutions and training psychological counselors in cognitive-behavioral methods to support students’ mental well-being.